The Meaning Difference of Lexicon “Sakit” in Bimanese: A Semantic Perspective - Umar, Umar (e-Journal of Linguistics, 2020)
The current study attempts to describe the lexicon “sakit” in Bimanese used by Mbojo ethnic group in daily communication and analyze the meaning difference from the semantic perspective. The research applied descriptive qualitative method of analysis and the data were collected by using fishbowl, recording, and note taking technique. Based on the data analysis the findings reveal that thirteen lexicons “sakit“ are used by Mbojo ethnic group in daily communication including supu [supu], hengge [hengge], sari’i [sari’i], rambo [rambo], mbalo [mbalo], mancoro [mancoro], kantero [kantero], duha [duha], pili [pili], ngelu [ngelu], ncara oi [ncara ?wi], mbowi [mb ?wi] and winte [winte].